Generalforsamling i Steno Museets Venner den 28. marts 2001 kl. 19.30 på Steno Museet - Grøn, Bjarning (Stenomusen, 2001)
Generalforsamling i Steno Museets Venner den 28. marts 2001 kl. 19.30 på Steno Museet